Does foreign direct investment lead to productivity spillovers? Firm level evidence from Indonesia - Suyanto, Suyanto; Salim, Ruhul; Bloch, Harry (Pergamon, 2009)
This paper examines whether spillovers from foreign direct investment (FDI) make any contribution to productivity growth in the Indonesian chemical and pharmaceutical firms using plant-level panel data. The spillover effects from FDI are analyzed using a stochastic frontier approach and productivity growth is decomposed using a generalized Malmquist output-oriented index. The results show positive productivity spillovers from FDI; higher competition is associated with larger spillovers; and domestic firms with R&D gain more spillover benefits compared to those without R&D. FDI spillovers are found to be positive and significant for technological progress and positive, but not significant, for technical and scale efficiency change.